Clinical Actual Use Human Factors Testing. Issue 1 (June 2018) - Shannon Clark, P.E.; Forkey, Denise
Due to perceived cost and time savings, medical device and combination product manufacturers frequently consider the option to combine human factors testing with clinical studies. There are some scenarios in which human factors and clinical testing of medical products can be combined to save time and resources. While guidance documents published by the Food and Drug Administration (FDA) emphasize that most human factors validation testing can fully evaluate use-related safety via simulated use usability testing, there are some cases in which clinical actual use usability testing is needed to fully evaluate use-related safety. This paper suggests synergies between clinical testing and human factors testing, presents challenges faced by human factors practitioners when the two types of testing are combined, and offers best practice recommendations to maximize the chance of successfully evaluating the human factors endpoints.